2008
DOI: 10.1021/jp8073464
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamics in Complex Environments: Ab Initio Multiple Spawning Quantum Mechanical/Molecular Mechanical Dynamics

Abstract: Our picture of reactions on electronically excited states has evolved considerably in recent years, due to advances in our understanding of points of degeneracy between different electronic states, termed "conical intersections" (CIs). CIs serve as funnels for population transfer between different electronic states, and play a central role in ultrafast photochemistry. Because most practical photochemistry occurs in solution and protein environments, it is important to understand the role complex environments p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
246
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 262 publications
(272 citation statements)
references
References 115 publications
17
246
0
2
Order By: Relevance
“…These energy barriers experienced by the chromophore during isomerization are caused by the protein environment as shown by model GFP chromophores, which isomerize efficiently instead of fluorescing in fluid solutions unless frozen (32)(33)(34)(35). This viewpoint is also supported by various computational studies (24,(36)(37)(38)(39). The existence of these large excited-state energy barriers leads to strong fluorescence in GFPs in contrast to other proteins, such as rhodopsin (40) and photoactive yellow protein (PYP) (41), that generically have similar PESs (Results and Discussion, A Unifying Scheme of Fluorescent and Photosensory Proteins) but are optimized for cis-trans isomerization instead of fluorescence.…”
Section: Resultsmentioning
confidence: 83%
“…These energy barriers experienced by the chromophore during isomerization are caused by the protein environment as shown by model GFP chromophores, which isomerize efficiently instead of fluorescing in fluid solutions unless frozen (32)(33)(34)(35). This viewpoint is also supported by various computational studies (24,(36)(37)(38)(39). The existence of these large excited-state energy barriers leads to strong fluorescence in GFPs in contrast to other proteins, such as rhodopsin (40) and photoactive yellow protein (PYP) (41), that generically have similar PESs (Results and Discussion, A Unifying Scheme of Fluorescent and Photosensory Proteins) but are optimized for cis-trans isomerization instead of fluorescence.…”
Section: Resultsmentioning
confidence: 83%
“…Further developments 12 of GPU-SA-CASSCF/AIMS will include solvent and relativistic (intersystem crossing) effects to improve the comparison between theory and experiment. [70][71][72] …”
mentioning
confidence: 99%
“…In these papers, it was shown that solvent effects determined the placement and energy of conical intersection seams, as well as the coordinates that accessed them. A tendency for charge-transfer conical intersections to be stabilized by solvents excited-state potential in solvated systems has been observed in excited-state dynamics simulations 51,52 .…”
Section: Introductionmentioning
confidence: 93%